Analysis of Beneficial Owner Comparison in Tax Treaty between Indonesia-Hong Kong and Indonesia-Netherlands - Jimmy Jimmy; Meilani Meilani (Journal of Accounting and Management Innovation, 2023)
Research found that implementing a tax treaty agreement can assist a country in increasing its economic growth, besides to prevent the imposition of double taxation as its main goal. Indonesia has already signed many tax treaty agreements with countries around the world, such as with Hong Kong and Netherlands that have been discussed most until today. The purpose of this research are to compare the different of beneficial owner application in tax treaty between Indonesia-Hong Kong and Indonesia-Netherlands on passive income such as dividends, interest, and royalties and to know the positive and negative impacts that can effect to Indonesia under having these tax treaty agreements. The research design and method used in this research is qualitative descriptive method along with literature research and using secondary data. The Indonesia-Netherlands tax treaty is one of Indonesia’s biggest tax leaks with 27 cases of disputes and resulting in big tax losses for Indonesia. Contrarily, no cases of disputes have been found related to the tax treaty agreement between Indonesia-Hong Kong up to now. Moreover, Indonesia and Hong Kong’s tax treaty agreement are also significantly bringing more investor from Hong Kong to Indonesia rather than from the Netherlands. This research concludes that Indonesia should establish more tax treaty agreement especially with the country that has a lot of economic activities with the aim to prevent the imposition of double taxation and also given an opportunity for Indonesia to enhance economic growth as well as also to increase the tax revenue. Keywords: Tax Treaty, Double Taxation, Beneficial Owner, Economic Growth, Indonesia, Hong Kong, Netherlands